The Role of Local Communities in Tuna Conservation in North Maluku - Ibnu W. Laitupa; Sitkun Deni; Jufri P. Laitupa; Abdussabar Polanunu; Ruslan A. Deng (BIOSAINSTEK, 2026)
Tuna is a valuable international commodity, but its population in North Maluku is facing a significant decline due to unsustainable fishing practices and overexploitation. Conservation efforts are crucial, and the role of local communities is indispensable, as they possess traditional knowledge and experience vital for sustainability. Approximately 70% of the coastal population in North Maluku depends on the fisheries sector, making them key economic actors and guardians of the ecosystem. Various initiatives, such as the Community-Based Fisheries Management (CBFM) program, aim to empower local communities in resource management and supervision, leading to increased conservation awareness and reduced harmful fishing practices. Education and training on sustainable techniques are also essential for active contribution to conservation. However, the conservation efforts face several challenges, including illegal, unreported, and unregulated (IUU) fishing, which significantly damages tuna populations. Additionally, conflicts of interest with large commercial fishing companies and the impacts of climate change threaten local livelihoods and the marine ecosystem. Local wisdom, such as the traditional "sasi" system (temporary closure of fishing areas), proves effective in allowing fish stocks to recover. The collective management of marine resources, through the formation of fishermen groups, enhances the monitoring and enforcement of regulations. Ultimately, a collaborative approach involving the government, NGOs, and local communities is necessary to create effective and sustainable solutions for tuna conservation in North Maluku.